Pengaruh Model Pembelajaran TGT Pada Hasil Belajar Siswa Mata Pelajaran Akidah Akhlak di MA Al-Bairuny - Wardani, Dian Kusuma; Alaul Huda, Saihul Atho’; AL-Adawiyah, Robiatul Al (JoEMS (Journal of Education and Management Studies), 2022)
The purpose of this study was to determine the TGT learning model on the learning outcomes of class X students at MA Al-Bairuny Jombang. The method used is the experimental method. In this study, the research subjects were students of class X IPS I as an experimental class using the TGT learning model and class X IPS II as a control class using the lecture method. The data analysis technique used the "t" test and the significance level used was 0.05. The results of this study indicate that the use of the TGT learning method has an influence on student learning outcomes in the Akidah Akhlak subject. This is evidenced by the results of hypothesis testing using the t-test, which is significant (0.000) < (0.05) so that Ho is rejected. Thus, it shows that the TGT learning model has a significant influence on learning outcomes. From this research, it can be said that the TGT learning model has a fairly good effect compared to the lecture method.